2016
DOI: 10.1111/cge.12820
|View full text |Cite
|
Sign up to set email alerts
|

EMRdocumentation of physician–patient communication following genomic counseling for actionable complex disease and pharmacogenomic results

Abstract: Genomic risk information for potentially actionable complex diseases and pharmacogenomics communicated through genomic counseling may motivate physicians and patients to take preventive actions. The Ohio State University-Coriell Personalized Medicine Collaborative is a randomized trial to measure the effects of in-person genomic counseling on chronic disease patients provided with multiplex results. Nine personalized genomic risk reports were provided to patients through a web portal, and to physicians via ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 33 publications
(36 reference statements)
0
10
0
Order By: Relevance
“…As pharmacogenomic results become increasingly available at the pointof-care, it is important to assess patient-provider communications and implications of results delivery, as these considerations will affect widespread adoption [12][13][14] . A limited amount of research has suggested that pharmacogenomic results may positively influence doctorpatient communications 15,16 . Feelings of shared decision-making between patient and provider in the context of pharmacogenomic results may also positively impact prescribing communications 15 .…”
Section: Introductionmentioning
confidence: 99%
“…As pharmacogenomic results become increasingly available at the pointof-care, it is important to assess patient-provider communications and implications of results delivery, as these considerations will affect widespread adoption [12][13][14] . A limited amount of research has suggested that pharmacogenomic results may positively influence doctorpatient communications 15,16 . Feelings of shared decision-making between patient and provider in the context of pharmacogenomic results may also positively impact prescribing communications 15 .…”
Section: Introductionmentioning
confidence: 99%
“…The CPMC web portal also offers text and multimedia format educational materials and tools that enable study participants to learn more about basic genetics concepts, complex disease genetics, pharmacogenetics, family history risk, relative risk and health condition specific summaries detailing disease etiology, risk factors, treatment and available preventative or risk reducing actions. Results from primary outcomes of various trials related to the CPMC have been previously reported (Gordon et al, 2012; Schmidlen et al, 2016; Schmidlen et al, 2014; Sweet et al, 2016). …”
Section: Methodsmentioning
confidence: 99%
“…Results from primary outcomes of various trials related to the CPMC have been previously reported (Gordon et al, 2012; Schmidlen T, 2016; Schmidlen et al, 2014; Sweet K, 2016). For this qualitative interview study, participants were either from the Ohio State University chronic disease cohort (OSU-CPMC) comprised of individuals diagnosed with either hypertension or congestive heart failure (n=199) or the CPMC cohort.…”
Section: Methodsmentioning
confidence: 99%